A Qualitative Tool to Guide in the Interpretation of the Numerical Rating Scale for Pruritus Intensity in Patients with Atopic Dermatitis - Ignasi Figueras; Marta Feito; Marta García-Bustinduy; Emilio Monte-Boquet; Sandra Ros; Violeta Zaragoza; África Luca de Tena; Francisco Javier Ortiz de Frutos (Medical Journals Sweden, 2024)
Atopic dermatitis is a cutaneous inflammatory disease characterized by intense pruritus, which is often underestimated despite its direct impact on patients' health-related quality of life and the high burden it poses. The authors' goal was to design a qualitative tool to guide patients and healthcare professionals in their assessment and interpretation of pruritus intensity using a numerical rating scale. The draft of this tool, henceforth "guideline", was developed based on a systematic literature review and focus groups comprising patients and a scientific committee. This draft was validated with an independent group of patients and the final version was designed following their feedback. According to the results of the systematic review, pruritus impacts 6 health-related quality of life domains: sleep quality; emotional status; overall health-related quality of life; physical function; social/sexual activity; productivity, particularly affecting sleep quality and the emotional domain. Patients considered that physical function was the most strongly affected domain, followed by sleep quality and emotional well-being, establishing that a minimum pruritus intensity of 4 and 7 points impacts moderately and severely, respectively, on the different domains of patients' health- related quality of life. The guideline may help patients and healthcare professionals to interpret and assess pruritus intensity using a numerical rating scale and to understand the impact of pruritus on patients' health-related quality of life.